2009
DOI: 10.1086/644757
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Checklist of Hospital Interventions to Decrease the Incidence of Healthcare-Associated Clostridium difficile Infection

Abstract: Our intervention was successful in reducing the incidence of CDI at our hospital. On the basis of our experience, we propose the use of a checklist of hospital interventions to decrease the incidence of healthcare-associated CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 25 publications
0
45
0
Order By: Relevance
“…This study was an observational before–after study of adult patients admitted to a tertiary university-affiliated hospital during a 4-year period from January 2004 to December 2008 42. The intervention included an educational campaign, a prevention bundle, and a treatment bundle.…”
Section: Infection Control and Prevention Strategiesmentioning
confidence: 99%
“…This study was an observational before–after study of adult patients admitted to a tertiary university-affiliated hospital during a 4-year period from January 2004 to December 2008 42. The intervention included an educational campaign, a prevention bundle, and a treatment bundle.…”
Section: Infection Control and Prevention Strategiesmentioning
confidence: 99%
“…49 Abbett et al. 50 and Salgado et al. 51 describe the use of a C. difficile prevention bundle in their university-affiliated tertiary care facilities.…”
Section: Resultsmentioning
confidence: 99%
“…In the UK, the frequency of Table 1 Overall incidence of C difficile episodes, incidence in A-ICUs, and incidence in the remaining hospital units [19]. Previous studies have suggested the efficacy of specific infection control measures in reducing the incidence of CDI [20][21][22]. Rapid diagnosis of CDI is essential to improve patient outcome and prevent disease transmission.…”
Section: Discussionmentioning
confidence: 99%